Watchful waiting of the neck in early stage oral cancer is unfavourable for patients with occult nodal disease. Issue 8 (August 2016) - Dik, E.A.; Willems, S.M.; Ipenburg, N.A.; Rosenberg, A.J.W.P.; Van Cann, E.M.; van Es, R.J.J.
Abstract: For cT1/2N0 oral squamous cell carcinoma (OSCC), treatment of the neck is a matter of debate. Two treatment strategies were evaluated in this study: selective neck dissection (SND) and watchful waiting (WW). One hundred and twenty-three SND patients and 70 WW patients with cT1/T2N0M0 OSCC of the tongue, floor of mouth, or buccal mucosa were analysed retrospectively. Extracapsular spread (ECS), 3-year overall survival (OS), and disease-specific survival (DSS) were determined. Twenty-nine percent of SND patients and 13% of WW patients had occult nodal disease. WW-N+ patients showed thicker tumours as compared to WW-N0 patients (5 mm vs. 2 mm, P  = 0.02). WW-N+ patients showed significantly more ECS as compared to SND-N+ patients (56% vs. 14%, P  = 0.016) and had a significantly worse 3-year DSS than SND-N+ patients (56% vs. 82%, P  = 0.02). For T1 OSCCs, a watchful waiting policy is acceptable if tumour thickness proves to be <4 mm. Otherwise, an additional treatment of the neck is advised, since WW-N+ patients show more ECS, with a worse DSS than SND-N+ patients.